Comparison of Non-Specific Standardization of Moringa (Moringa oleifera): A Systematic Literature Review - Chaerunnisa; Erisa Mindawati; Nurhalimah; Siti Solihat; Wida Nurhamidah; Lia Fikayuniar (HM Publisher, 2023)
In an effort to ensure that Moringa oleifera products available on the market meet certain standards, including cleanliness, authenticity, and safety, non-specific standardization is carried out. This study aimed to carry out a systematic review to explore the non-specific standardization of Moringa oleifera. The literature search process was carried out on various databases (PubMed, Web of Sciences, EMBASE, Cochrane Libraries, and Google Scholar) regarding the comparison of non-specific standardization of Moringa oleifera. This study follows the preferred reporting items for systematic reviews and meta-analysis (PRISMA) recommendations. The non-specific standardization process for Moringa oleifera involves botanical identification, evaluation of appearance and organoleptic characteristics, measurement of water, ash, and fiber content, as well as microbiological testing and pesticide residues.